Degradation and removal methods of antibiotics from aqueous matrices - A review - Vera Homem (2011)
Over the past few years, antibiotics have been considered emerging pollutants due to their continuous input and persistence in the aquatic ecosystem even at low concentrations. They have been detected worldwide in environmental matrices, indicating their ineffective removal from water and wastewater using conventional treatment methods. To prevent this contamination, several processes to degrade/remove antibiotics have been studied. This review addresses the current state of knowledge concerning the input sources, occurrence and mainly the degradation and removal processes applied to a specific class of micropollutants, the antibiotics. In this paper, different remediation techniques were evaluated and compared, such as conventional techniques (biological processes, filtration, coagulation, flocculation and sedimentation), advanced oxidation processes (AOPs), adsorption, membrane processes and combined methods. In this study, it was found that ozonation, Fenton/photo-Fenton and semiconductor photocatalysis were the most tested methodologies. Combined processes seem to be the best solution for the treatment of effluents containing antibiotics, especially those using renewable energy and by-products materials.